Safety of dexamethasone intravitreal implant injections for treatment of macular edema related to retinal vein occlusion - Gouveia, Petra (2016)
Purpose: To assess the safety of the dexamethasone implant in the treatment of macular edema (ME) secondary to retinal vein occlusions. Material and Methods: Retrospective study of patients with ME secondary to central retinal vein occlusion (CRVO) or branch retinal vein occlusion (BRVO) treated with dexamethasone implant (Ozurdex, Allergan Inc, Irvine, CA) from January 2011 through August 2015. Safety assessment included analysis of cataract progression, intra-ocular pressure (IOP) changes, antihypertensive eye drops requirement and/or glaucoma surgery. Results: Twenty-four eyes (24 patients) were included in the study, 58% female. Mean age was 66.5 years (49 – 95 years). Thirteen BRVO and 11 CRVO were treated in this series. 75% had history of previous treatment (laser, intravitreal injections or vitrectomy). In six patients (25%) the implant was used as first-line therapy. Twenty patients (83.0%) were phakic in the beginning of the study. Cataract progression was observed in two patients, though none required cataract surgery. Ocular hypertension (IOP>21mmHg) was documented in seven patients (29.1%) following treatment and control was reached with antihypertensive eye drops. A mean 3.53 mmHg elevation of IOP wasn’t statistically significant. The subgroup analysis of BRVO and CRVO did not detect differences in the following parameters: cataract progression, cataract surgery, IOP elevation and hypotensive drug requirement. Conclusions: The dexamethasone implant is an important therapeutic tool for ME secondary to retinal vein occlusions. In this series, cataract progression was negligible, though 83% of our patients were phakic. The IOP elevation, observed in 30% of patients, was readily managed with antihypertensive drops.